If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 3) + 26 = (x + 5)(x + 2) Reorder the terms: x(3 + x) + 26 = (x + 5)(x + 2) (3 * x + x * x) + 26 = (x + 5)(x + 2) (3x + x2) + 26 = (x + 5)(x + 2) Reorder the terms: 26 + 3x + x2 = (x + 5)(x + 2) Reorder the terms: 26 + 3x + x2 = (5 + x)(x + 2) Reorder the terms: 26 + 3x + x2 = (5 + x)(2 + x) Multiply (5 + x) * (2 + x) 26 + 3x + x2 = (5(2 + x) + x(2 + x)) 26 + 3x + x2 = ((2 * 5 + x * 5) + x(2 + x)) 26 + 3x + x2 = ((10 + 5x) + x(2 + x)) 26 + 3x + x2 = (10 + 5x + (2 * x + x * x)) 26 + 3x + x2 = (10 + 5x + (2x + x2)) Combine like terms: 5x + 2x = 7x 26 + 3x + x2 = (10 + 7x + x2) Add '-1x2' to each side of the equation. 26 + 3x + x2 + -1x2 = 10 + 7x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 26 + 3x + 0 = 10 + 7x + x2 + -1x2 26 + 3x = 10 + 7x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 26 + 3x = 10 + 7x + 0 26 + 3x = 10 + 7x Solving 26 + 3x = 10 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 26 + 3x + -7x = 10 + 7x + -7x Combine like terms: 3x + -7x = -4x 26 + -4x = 10 + 7x + -7x Combine like terms: 7x + -7x = 0 26 + -4x = 10 + 0 26 + -4x = 10 Add '-26' to each side of the equation. 26 + -26 + -4x = 10 + -26 Combine like terms: 26 + -26 = 0 0 + -4x = 10 + -26 -4x = 10 + -26 Combine like terms: 10 + -26 = -16 -4x = -16 Divide each side by '-4'. x = 4 Simplifying x = 4
| 2*5x^3=5x^3 | | 15x-122=5x-12 | | x+119y=181 | | 148-3x=42x+23 | | x+y=181 | | (7/12x)-1/3=(3/8x)-5/6 | | x(x+3)+26=(x+6)(x+2) | | x+9=181 | | (2/5x)-1/4=(3/10x)-4/5 | | 6x^2+54x=9 | | xy+yz= | | 144-2x=43x+24 | | 5s+8s= | | 3a+af= | | -4p-8/3+2p=-10/3 | | t+1/2=t+9/4+1-7/4 | | 144x/3x | | y=(-416.72*81)+(4416.7*9)+8500 | | 4x-3y+14=0 | | 33x-44y+99= | | 188-7x=38x+18 | | -2m+34-7(m-3)=8m-(5m-7)-6m+6 | | 60r+40s-100t= | | 14-7x=41-28x | | 4x=5x+2 | | 21p-49q-7= | | 85-5x=9x+19 | | y=(-143.3*81)+(1823.3*9)+6820 | | 2(x-6)=3x(-218) | | 12p-30q+36= | | 2*3.14*r=7.51 | | 7x-9x+6=-4x+6 |